2006
DOI: 10.1073/pnas.0508005103
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of sensory neuron mechanotransduction by PKC- and nerve growth factor-dependent pathways

Abstract: Many sensations of pain are evoked by mechanical stimuli, and in inflammatory conditions, sensitivity to such stimuli is commonly increased. Here we used cultured sensory neurons as a model of the peripheral terminal to investigate the effects of inflammatory signaling pathways on mechanosensitive ion channels. Activation of two of these pathways enhanced transduction in a major population of nociceptors. The proinflammatory neurotrophin nerve growth factor caused an up-regulation of mechanically activated cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
70
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 72 publications
(77 citation statements)
references
References 48 publications
5
70
2
Order By: Relevance
“…This potentiation is much greater than the enhancement of RA-MA currents shown previously following the treatment of primary afferent neurons with inflammatory mediators or protein kinase C activators (12,13). Previous studies have shown that functions of Piezo2 chan- , n ϭ 8).…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…This potentiation is much greater than the enhancement of RA-MA currents shown previously following the treatment of primary afferent neurons with inflammatory mediators or protein kinase C activators (12,13). Previous studies have shown that functions of Piezo2 chan- , n ϭ 8).…”
Section: Discussionmentioning
confidence: 53%
“…An arrow indicates the time when the solutions are injected into the hind paws. Data represent mean Ϯ S.E., *, p Ͻ 0.05; **, p Ͻ 0.01. nels can be up-regulated through intracellular signaling pathways, including protein kinase A, protein kinase C, and EPAC1 (12,13,15), raising the possibility that osmotic swelling-induced sensitization of RA-MA channels in our study may also be mediated by these intracellular signaling pathways. Osmotic swelling may activate TRPV4 channels (28) to increase intracellular Ca 2ϩ concentrations, which may subsequently activate intracellular second messenger systems to up-regulate RA-MA channel functions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the expression of channels in sensory neurons that contribute to mechanosensation has been shown to be up-regulated both transcriptionally and in terms of membrane trafficking by inflammatory mediators, the development of allodynia has often been associated with events in the dorsal horn (14). Intriguingly, many peptide mediators associated with small-diameter sensory neurons [calcitonin gene-related peptide (CGRP), substance P, brain-derived neurotrophic factor (BDNF)] have been shown to evoke allodynia when applied intrathecally (15)(16)(17).…”
Section: Mechanisms Of Allodyniamentioning
confidence: 99%